The effect of some organic compounds and NAA application on the in vitro growth of the black orchid (Coelogyne pandurata Lindl.) - RINI UNTARI; DWI MURTI PUSPITANINGTYAS (Society for Indonesian Biodiversity, 2006)
Coelogyne pandurata Lindl. is a lowland epiphytic orchid that has pale green flowers with typically black markings on the lips. This species conventionally propagated asexually by rhizome. This orchid is now facing a great conservation problem and threatened to extinction due to human exploitation. That is why conservation activities such as developing proper cultivation, are urgently required. An in vitro experiment was conducted at the Laboratory of Tissue Culture at Bogor Botanic Garden. The experiment was carried out using a completely randomized design with two factors and ten replications. The treatments were the supplementation of the basal media i.e. Vacin and Went added with sugar, activated charcoal and agar, with 30 different combinations of organic compounds i.e., coconut water 250 mL/L, banana 150 g/L, potato 200 g/L, sweet potato 150 g/L, soybean 150 g/L and no organic compound as a control, and application of NAA (0, 5, 10, 15, and 20 ppm). The result showed that there was a significant effect of the organic compounds and NAA application on the length and the number of roots, height, number of leaves and number of shoots produced by the explants. The combination of sweet potato 150 g/L without NAA application showed the best result.Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: Coelogyne pandurata, organic compound, NAA, in vitro.